SERUM COPPER, ZINC AND SELENIUM LEVELS IN RHEUMATOID ARTHRITIS - Mesut Çolak; Namık Kemal Bingöl; Oğuz Ayhan; Şenel Avcı; Vedat Bulut (Archives of Rheumatology, 2001)
The objective of this study was to measure the alterations in some important serum trace elements, including selenium (Se), zinc (Zn), copper (Cu), in patients with rheumatoid arthritis (RA). In the study, serum trace elements were determined by using Atomic Absorption Spectrophotometer in sera of patients with RA (n=32), and statistically compared with healthy individuals (n=52). Serum Cu concentration was found significantly higher in patients group than those of healthy individuals (26,06±4,.71 and 17,74±3,30 µmol/L, respectively) (p<0,001). In contrary, Se and Zn levels were lower in patients (0,18±0,05 µmol/L and 6,58±3,14 µmol/L, respectively) according to the healthy subjects (0,21±0,06 µmol/L and 11.44±6,00 µmol/L, respectively). Our results showed that serum trace elements (Se, Zn and Cu) concentrations are altered in RA patients. The changes may be a part of autoimmune process in organism induced by cytokines. In conclusion, we suggest that decrease in Zn and Se levels and elevation in Cu levels are probably responsive to inflammation and resulted from defence strategies of organism and mediated by the hormone-like substances.